Respostas
respondido por:
0
a) achar valor de m
y2 -y1
m = ----------
x2 - x1
-5 +1
m = ------
2 + 3
-4
m = ----
5
substituir na formula os dados
y -y1 = m (x - x1)
y+1 = -4/5 ( x +3)
y+1 = -4/5x - 12/5
y= -4/5x -12/5 -1
y= -4x -12 -5
y = 4x -17
y2 -y1
m = ----------
x2 - x1
-5 +1
m = ------
2 + 3
-4
m = ----
5
substituir na formula os dados
y -y1 = m (x - x1)
y+1 = -4/5 ( x +3)
y+1 = -4/5x - 12/5
y= -4/5x -12/5 -1
y= -4x -12 -5
y = 4x -17
alexandretradep8q7a4:
desculpe está errada
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás